2002
DOI: 10.1073/pnas.032095099
|View full text |Cite
|
Sign up to set email alerts
|

Knotting probability of DNA molecules confined in restricted volumes: DNA knotting in phage capsids

Abstract: When linear double-stranded DNA is packed inside bacteriophage capsids, it becomes highly compacted. However, the phage is believed to be fully effective only if the DNA is not entangled. Nevertheless, when DNA is extracted from a tailless mutant of the P4 phage, DNA is found to be cyclic and knotted (probability of 0.95). The knot spectrum is very complex, and most of the knots have a large number of crossings. We quantified the frequency and crossing numbers of these knots and concluded that, for the P4 tail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
307
2
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 245 publications
(320 citation statements)
references
References 42 publications
(52 reference statements)
10
307
2
1
Order By: Relevance
“…DNA knotting probability is enhanced in P4 derivatives containing genome deletions (20) and in tailless mutants (21). We recently showed that most of these knots are formed by the cyclization of the DNA while it is confined inside the phage capsid (22). Here, we show that these knots capture information about the global arrangement of the packed DNA.…”
mentioning
confidence: 62%
See 2 more Smart Citations
“…DNA knotting probability is enhanced in P4 derivatives containing genome deletions (20) and in tailless mutants (21). We recently showed that most of these knots are formed by the cyclization of the DNA while it is confined inside the phage capsid (22). Here, we show that these knots capture information about the global arrangement of the packed DNA.…”
mentioning
confidence: 62%
“…Bacteriophage P4 vir1 del22 was prepared as described in ref. 22. Briefly, the phage was amplified in Escherichia coli strain C-1895, which is lysogenic for P2 (the helper prophage).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sufficiently long polymers, such as DNA, are likely to be entangled [1,2]. On the other hand, there are very few knotted RNA molecules -in a recent assessment [3] only three cases have been identified, but the corresponding structures are resolved poorly.…”
Section: Introductionmentioning
confidence: 99%
“…Arsuaga et al showed that the tight geometric confinement the genome is subjected to is a significant contributor to the knot formation [7,17]. Such bacteriophages are the "viruses of bacteria", and they work by releasing their DNA into the cytosol of their host.…”
Section: Introductionmentioning
confidence: 99%